Bulk precipitation, throughfall and stemflow deposition of n-nh4 +, n-nh3 and n-no3 - in an andean forest (2014)
This research evaluated the input flux of nitrogen (N) compounds, namely, NH4 +, NH3 and NO3 - through an Andean forest canopy adjacent to a semi-natural wetland in south-western Colombia, South America. The concentrations of these compounds were determined in the hydrological processes of bulk precipitation, total throughfall and total stemflow. Other variables examined were catchment volume, pH and conductivity. The estimated entry for N compounds showed that throughfall was the process that recorded the highest weighted flux averages of N-NO3 - (1.34 kg ha-1 month-1), N-NH4 + (0.15 kg ha-1 month-1) and N-NH3 (< 0.001 kg ha-1 month-1) over the sampling period. Results indicated that the forest canopy acted as a living barrier that retained emissions of man-made N compounds. This research contributed to the analysis of the transformation of nutrient input fluxes via bulk precipitation, throughfall and stemflow to provide better understanding of the biogeochemical functioning of tropical wetlands that are influenced by atmospheric inputs from natural and anthropic sources.